Informal learning as a tool of training and development in SMEs - Hanif, Hanapi (Universiti Malaysia Sarawak (UNIMAS), 2015)
This research aims to study about training and development in small and medium sized enterprise (SMEs), which only focus on informal learning. This study have been conducted in Kuching and Kota Samarahan, which include micro, small, and medium sized company that come from various business background. This study engages a survey design. Seven informants are purposively selected to be involved in the survey. An open-ended questionnaire was used in the data collection. The data obtained are analyzed by way of content analysis. The fmdings suggest that SMEs practice many types of informal learning. Even though they have problem with it, they still practioed informal learning because they have motivation to learn. Moreover, they learn many competencies through informal learning.